Classroom Management of Senior and Yunior English Teachers in Medan - Masitowarni Siregar (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
The purpose of the study was to find out the differences between the classroom management performed by the senior and yunior teachers in teaching English at senior High School in Medan. This is a descriptive qualitative study. The respondents of the research were 28 English teachers of Yunior and Senior High School in Medan. Questionnaire and Observation sheet were used to collect the data on the teachers classroom management. The result of the study shows that senior English teachers perform more aspects of Classroom management. They perform 18 point from 20 points aspect.. Junior English teacher get 17 point. Although senior teachers perfom only show slightly more aspect of classromm management but for the quality of classroom management they perform better due to the longer experience of teaching. For junior English teacher they perform more enthusiastics energy, although it is clear that they have to study more on the behavior and attitude expected in the classrooms.